"Shift from Teaching to Learning"- kritische Reflexion anhand des Wertequadrats. Am Beispiel von "Menon" - Palekčić, Marko (Array, 2008)
A Shift from Teaching to Learning - A critical reflection based on the Square of Values. On the example of „ Menon“ . The relationship between teaching and learning in contemporary didactics is discussed from the perspective of the shift from teaching to (self)learning. A new culture of learning, a new paradigm is being discussed. The author bases his critical reflection of this new paradigm on the application of the Square of Values (according to Helwig, 1967). The concrete application of the Square of Values, specified by the author as the Square of Education, emanates from the analysis of the relationship between teaching and learning, from the didactic perspective, in the „ Menon“ document. The main result of the analysis shows that the relationship between teaching and learning can be better understood as the dialectic relational tension between two „ sister virtues“ of teaching (as demonstration) and learning (as insight), i.e. as the and/and relationship, than as the one-sided transfer from teaching (negatively defined as tuition and/or mere instruction) to learning (conceived as recall), i.e. as the relationship (either/or) between two extreme non-values, which can be considered as the main feature of the so called new culture of learning.